SCIENTIFIC PRINCIPLES OF THE DEVELOPMENT OF EDUCATIONAL-SCIENTIFIC PROGRAM FOR THE TRAINING OF DOCTORS OF PHILOSOPHY IN THE SPECIALTY 011 "EDUCATIONAL, PEDAGOGICAL SCIENCES" AT ZHYTOMYR IVAN FRANK STATE UNIVERSITY (Innovative professional education, 2022)
The aim of the post-graduate course in the field of knowledge 01 Education /Pedagogy is to train highly qualified scientific-pedagogical personnel capable of carrying outresearch-innovative, scientific-pedagogical activities and solving current problems in the field ofeducation. It corresponds to modern requirements for the training of competent, competitivespecialists integrated into the world-wide and European educational spaces. The presentedapproaches to the development of the educational-scientific program for the training of Doctorof Philosophy in the specialty 011 "Educational, pedagogical sciences" at Zhytomyr Ivan FrankoState University allow to inlay the conceptual foundations of this process as well as to analyzethe results aimed at identifying corresponding achievements, problems, and prospects.
Keywords: postgraduate studies, training of third (scientific) level of higher education, educational-scientific program